(untitled) (Scientific journal of the Fergana State University, 2025)
This article covers the economic indicators, areas of activity, achieved productivity and employment of agro-industrial clusters in Samarkand region. Also, the level of technical efficiency, that is, the conversion of resources into income, was analyzed using data coverage analysis of the largest cotton-textile clusters in the region: “Afrosiyob Jeans Textile” and “Samarkand Kamalak Invest Textile”.